2015
DOI: 10.1039/c5ra13253c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of amidoxime surface-functionalized polyindole (ASFPI) nanofibers for Pb(ii) and Cd(ii) adsorption from aqueous solutions

Abstract: Amidoxime surface-functionalized polyindole (ASFPI) nanofibers were prepared by electrospinning of chemically synthesized poly(5-cyanoindole) followed by surface modification. The as-prepared ASFPI nanofibers were characterized with FTIR, SEM, BET surface areas and water contact angle measurement.Meanwhile, the adsorption properties and mechanism of ASFPI nanofibers towards Pb(II) and Cd(II) in aqueous solution were mainly investigated by a batch method. It was found that ASFPI nanofibers showed a high affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 40 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…For example, PIN nanofibers were used for adsorption of copper (II) by Zhijiang et al [ 12 ]. Similarly, Cai, Z. et al [ 13 , 14 ] prepared surface-functionalized PIN nanofibers for effective removal of Cr(VI), Pb(II), and Cd(II) from aqueous solutions. Besides, polyacrylonitrile/PIN composite and zinc oxide/magnesium oxide/PIN have been used for Cu(II) and Pb(II), respectively [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PIN nanofibers were used for adsorption of copper (II) by Zhijiang et al [ 12 ]. Similarly, Cai, Z. et al [ 13 , 14 ] prepared surface-functionalized PIN nanofibers for effective removal of Cr(VI), Pb(II), and Cd(II) from aqueous solutions. Besides, polyacrylonitrile/PIN composite and zinc oxide/magnesium oxide/PIN have been used for Cu(II) and Pb(II), respectively [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylonitrile (PAN) and Super P (active carbon) were mixed with DMF to get a PAN/C slurry and was coated on the surface of CF to get PAN/C@CF (PCCF). After reaction with hydroxylamine hydrochloride, most of the nitrile groups are replaced by amidoxime groups, forming the modified electrode, herein referred to as PAN-ami/C@CF (PACCF). As seen by SEM, this amidoxime-modified CF consists of fibers with 20 μm diameter that were coated with a very thin polymer layer (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been demonstrated that an increase in the initial metal ion contributes to overcome mass transfer resistance between solid/solution interfaces. 40,41…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been demonstrated that an increase in the initial metal ion contributes to overcome mass transfer resistance between solid/solution interfaces. 40,41 The fabricated mats are extremely stable in water, easy to handle, and robust, thus allowing for a prolonged use (up to complete removal of ionic species) without any release of both fibrous material as well as adsorbed species.…”
Section: ■ Conclusionmentioning
confidence: 99%